PEMBUATAN ECO-ENZIM UNTUK PUPUK PERTANIAN BERKELANJUTAN DI DESA PELABUHAN DALAM, OGAN ILIR - Edward Saleh; M Umar Harun; Satria Jaya Priatna; KH Iskandar; Vincentia Veni Vera; Ressy Angli Permatasari (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
The price of chemical fertilizers is currently increasing and increasingly unaffordable for farmers, and their availability is increasingly scarce. Farmers really need fertilizer so that their plants can produce optimally, as an alternative substitution is organic fertilizer using eco-enzyme. Eco-enzyme liquid is the result of fermentation of a mixture of sugar (molasses), organic materials (fruit and vegetable waste), and water with a ratio of 1:3:10 for three months, in an airtight container. The target of this community service is farmers in Pelabuhan Dalam village, and Agricultural Extension Workers (AEW) in Pemulutan District, Ogan Ilir Regency. The purpose of this activity is to provide farmers and AEW with the ability to make eco-enzymes, improve farmers' ability to provide and obtain alternative fertilizers to substitute chemical fertilizers, and provide farmers with skills in applying eco-enzymes as fertilizers. The methods used are socialization with socialization, counseling, eco-enzyme making practices, eco-enzyme applications and mentoring. The results of the community service program have provided farmers and agricultural extension workers (PPL) with the knowledge and skills regarding eco-enzymes and their applications in agriculture. Following this program, 100% of the target audience is capable of making their own eco-enzymes and applying them directly as fertilizer. Furthermore, approximately 40% of the participants have independently produced eco-enzymes, while 60% prefer purchasing the finished product over making it themselves.